Mangifera L. - Mukherjee, S.K.; International Board for Plant Genetic Resources (1985)
This is the first of a series which summarizes studies of the geographical distribution of species, in this case those related to the cultivated mango with the purpose of devising a plan of action for collection and conservation (in situ and ex situ).